1997
DOI: 10.1124/mol.51.6.963
|View full text |Cite
|
Sign up to set email alerts
|

DNA Elements Recognizing NF-Y and Sp1 Regulate the Human Multidrug-Resistance Gene Promoter

Abstract: Regulation of the human multidrug resistance gene (hMDR1) was studied by mapping DNA elements in the proximal promoter necessary for efficient transcription. Transient transfection analysis in tumor cell lines (HCT116, HepG2, and Saos2) of promoter deletions identified several regulatory domains. These cell lines expressed hMDR1 mRNA. Removal of an element between +25 and +158 reduced promoter activity by 2-3-fold, whereas deletion of sequences from approximately -5000 to -138 base pairs gave a approximately 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
61
0

Year Published

1998
1998
2013
2013

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(69 citation statements)
references
References 36 publications
8
61
0
Order By: Relevance
“…24 For example, Sp1 binds to a GC element within the pgp-1 promoter and is required for its basal expression in a number of cell lines. 25,26 The complex formed between the 330bp segment and hCMEC/D3 nuclear extract indicated a large DNA-binding protein associated with the promotor. Thus it is possible that an Sp-family member is a component of this complex.…”
Section: Discussionmentioning
confidence: 99%
“…24 For example, Sp1 binds to a GC element within the pgp-1 promoter and is required for its basal expression in a number of cell lines. 25,26 The complex formed between the 330bp segment and hCMEC/D3 nuclear extract indicated a large DNA-binding protein associated with the promotor. Thus it is possible that an Sp-family member is a component of this complex.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, several labs showed that NF-Y is the activator, both under basal and under multiple inducing conditions. [102][103][104][105][106][107][108] In EMSAs performed with the Y/ CCAAT box, these authors detected NF-Y as the only DNAbinding complex. Specifically, Scotto's lab showed that a NF-YA dominant-negative mutant affects MDR1 expression.…”
Section: Nf-y Is the Sequence-specific Ccaat Factormentioning
confidence: 99%
“…Notably, the NF-Y binding site located at 782 to 773 mediates MDR1 activation by the histone deacetylase inhibitor trichostatin A and sodium butyrate (Jin and Scotto, 1998). This site, together with its adjacent Sp1 site (756 to 742), are important for the basal (Sundseth et al, 1997) and UV-induced up-regulation of MDR1 expression (Hu et al, 2000). A CAAT-like site (7120 to 7110) is involved in the upregulation of MDR1 in human drug-resistant HL60/ VCR line (Ogretmen and Safa, 2000).…”
Section: Role Of Nf-kb In Regulation Of Mdr1 Expression By 2-aafmentioning
confidence: 99%